Differences in Diet and Nutritional Status in Toddlers in Coastal and Mountainous Areas - Puji Lestari; Nurul Hidayati; Melya Ummunnisa (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Malnutrition of toddlers is often referred to as the golden age, which is irreversible. One of the factors that influence nutritional status is diet. The different geographical location between the coast and the mountains causes different food sources to be obtained. The purpose of this study was to analyze the differences in diet and nutritional status of toddlers in coastal and mountainous areas. This research design used a cross-sectional with sampling technique used stratified random sampling resulted in 143 toddlers. Data were obtained from direct interviews using the Semi Quantitative-Food Frequency Questionnare (SQ-FFQ) and nutritional status measurements using weight and height. The results showed that in coastal areas the majority of diets (energy, protein, fat, and carbohydrate) were good (90.9%), over (100%), good (67.5%) and good (85.7%). As for the majority of nutritional status in coastal areas, the weight for age (W/A) was normal (84.4%), height for age (H/A) was normal (92.2%), and weight for height (W/H) was normal (89.6%). In mountainous areas the majority of diets (energy, protein, fat, and carbohydrate) were over (57.6%), over (95.5%), over (60.6%) and good (68.2%). As for the majority of nutritional status in mountainous areas, the W/A was normal (96.96%), H/A was normal (71.21%) and W/H was normal (87.9%). The bivariate test showed there are difference energy and fat intake (p<0.05), but there are no difference protein dan carbohydrate intake (p> 0.05) between coastal and mountainous areas. The nutritional status have difference in H/A, but no differences in W/A and W/H in toddlers between coastal and mountainous areas.